Use of quality tools in optimizing the production process in dental prosthesis laboratory - de Moura, Luzinaldo Barreiros (2023)
This article demonstrates the importance of a management and optimization project in the production processes of a dental prosthetics laboratory. It explores the use of quality tools and their contributions to the success of improvement works, enhancing product quality and production flow. All strategic points of the company were restructured by managing change projects, ensuring each directive was aimed at achieving the necessary outcomes for successful planning. Focused on a complete transformation, each department experienced changes and soon witnessed results showcased in reports, including improvements in personnel, production, finances, and strategic management. These improvements aimed to secure new contracts and expand the portfolio of clients and suppliers.